2008
DOI: 10.1111/j.1365-3024.2008.01051.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation and structural changes of splenic lymphoid tissue in visceral leishmaniasis: A study on naturally infected dogs

Abstract: The aim of this study was to identify splenic immuno-inflammatory patterns associated with natural infection by Leishmania chagasi . Spleen samples were obtained from 72 stray dogs from an endemic area of visceral leishmaniasis. The animals were grouped into four categories as follows: (i) potentially resistant to visceral leishmaniasis, with a positive leishmanin skin test result, and negative splenic culture for Leishmania parasites (ii) potentially susceptible t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
99
1
6

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(118 citation statements)
references
References 42 publications
(52 reference statements)
12
99
1
6
Order By: Relevance
“…Our results coincided with others studies (GIUNCHETTI et al, 2008;LIMA et al, 2007;TAFURI et al, 1996), who observed well-organized intralobular granulomas in the livers of infected dogs. The disorganized tissue architecture in the spleen relating to predominance of parasitized macrophages was observed in our study and others researches (SANTANA et al, 2008;TASCA et al, 2009).…”
Section: Discussionsupporting
confidence: 84%
“…Our results coincided with others studies (GIUNCHETTI et al, 2008;LIMA et al, 2007;TAFURI et al, 1996), who observed well-organized intralobular granulomas in the livers of infected dogs. The disorganized tissue architecture in the spleen relating to predominance of parasitized macrophages was observed in our study and others researches (SANTANA et al, 2008;TASCA et al, 2009).…”
Section: Discussionsupporting
confidence: 84%
“…27 Lesions of the spleen of dogs with leishmaniasis are characterized by thickening of trabecular regions, granulomatous reaction and hemorrhagic areas, atrophy of lymphoid follicles and marginal zone, abundant macrophages with amastigotes in the cytoplasm, and perisplenitis. 36,39,50 Considering bacterial splenitis, dogs with Staphylococcus spp., 1 Mycobacterium avium Mycobacterium tuberculosis, 6,17,26,31 Listeria monocytogenes, 42 Bartonella henselae, and Bartonella vinsonii, 40 Clostridium spp., 2 Bacillus anthracis, 28 Burkholderia pseudomallei, 48 and multiple bacterial infection 11 have been described; in these cases, histologic lesions of the spleen are generally pyogranulomatous 6,40 or neutrophilic. 2 Splenic abscesses, likely due to bacterial infection, have been described in some dogs.…”
mentioning
confidence: 99%
“…is observed in vivo with a negative Montenegro test . Dogs infected with Leishmania infantum have a reduced number of T lymphocytes (Bourdoiseau et al, 1997) and a disruption of the splenic white pulp (Santana et al, 2008).…”
Section: Introductionmentioning
confidence: 99%